The impact of delayed reporting, assault type, victim gender, and victim-defendant familiarity on mock-juror's judgements - Pica, Emily (Applied psychology in criminal justice, 2021)
The current studies sought to examine whether assault type, among various extralegal variables, influenced mock-jurors' judgments. Study 1 investigated whether assault type (physical vs. sexual), delay in reporting (one year vs. ten years), and the victim's familiarity with the defendant (familiar vs. not familiar) influenced mock-jurors' judgments. Mock-jurors (N = 238) read a mock-trial transcript of either a physical or sexual assault that occurred at the victim's camp one year or ten years prior. The alleged perpetrator was a camp counselor that the victim had never met before or met their first year at the camp. Study 2 (N = 464) investigated whether assault type, delayed reporting, familiarity and victim gender were influential. The overarching theme present in the results is that sexual assault is perceived more negatively than physical assault as evidenced by higher guilt ratings and less favorable perceptions attributed to the defendant. Additionally, mock-jurors appear to be more hesitant to believe a victim who delayed her reporting of physical assault, compared to a delayed reporting of sexual assault. Implications of these findings and ideas for future research are discussed.